Influence Of microbial Phytase On Nutrient Utilization In Broilers - Balasubramanian D (Department of Poultry Science, College of Veterinary and Animal Sciences, 2000)
An eight week feeding trial usmg 180 day-old broiler chicks was conducted to study the influence of phytase supplementation (NatuphosR-5000) on nutrient utilization and subsequent performance. Treatments involved a standard broiler diet, a low available phosphorus (LAP) diet and the low available phosphorus diet plus graded levels of phytase at the rate of 500, 750 and 1000 units / kg diet. The groups fed standard broiler diet and low available phosphorus diets supplemented with 750 and 1000 units phytase showed significantly (P<O.OI) higher body weight and weight gain. The cumulative feed intake was statistically comparable among the experimental diets at sixth week, whereas, at eighth week it was significantly (P<0.05) lower in LAP diet without phytase than . that of other diets. The feed conversion ratio was significantly (P<0.0l) improved by the addition of phytase at 750 and 1000 units / kg in comparison to low available phosphorus diet. Graded levels of phytase addition linearly improved nitrogen retention while energy retention was significantly (P<O.Ol) higher in groups fed 750 and 1000 units of phytase / kg. The addition of 750 and 1000 units of phytase / kg diet significantly (P<O.OI) increased the availability of calcium while phosphorus availability was improved by all levels of enzyme 500, 750 and 1000 units / kg. The excretion of phosphorus was significantly (P<O.Ol) reduced in enzyme supplemented groups. The availability of manganese and zinc was significantly more in enzyme supplemented groups. Tibial ash, serum calcium and serum inorganic phosphorus were significantly (P<0.01) increased